Policy Innovation in the Public Sector: A Case Study of the Consulting Day on Friday Program at the Regional Inspectorate of Cirebon City - Muslimin, Ilham Fajar; Muhafidin, Didin (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2025)
This research was conducted with the aim of knowing how the innovation of the Consulting Day on Friday programme at the Cirebon City Regional Inspectorate. Several problems were found in the implementation of the programme innovation, causing the process to not run completely well. This is caused by several things related to regulations, human resources management, budgeting, innovation organisation, risk management, and knowledge contained in the innovation process of the Consulting Day on Friday program at the Cirebon City Regional Inspectorate. The theory used in this study is the OECD's (2017) theory of policy innovation, which explains that six aspects need to be considered in policy innovation: regulation, human resources management, budgeting, innovation organisation, risk management, and knowledge. This research uses qualitative research methods with data collection techniques through observation, interviews, and documentation. The informant determination technique used was purposive sampling technique with a total of 8 informants. The results showed that the implementation of the Consulting Day on Friday programme innovation has fulfilled the six dimensions of OECD policy innovation but has not fully run well, such as technical implementation guidelines that are still integrated with the usual consulting services, the formation of innovations has not been in accordance with central guidelines on regional innovation, risk management and prototypes are not carried out to minimise risks, have not utilised the potential for rewards and recognition of innovation, and the role of innovation organisations that has not yet had an impact.